Sustainable tourism supply chain in economic recession: Analysis of government intervention using game theory approach - Elham Sadat Mousavi (Sustainable Futures)
The tourism industry plays a vital role in both economic development and environmental sustainability but remains highly vulnerable to economic shocks. Government interventions, particularly tax policies, can significantly influence the stability and sustainability of tourism supply chains. This study investigates how government taxation and policy strategies affect a supply chain involving two five-star hotels, one adopting green practices and one operating conventionally, and an online travel agency (OTA). Using a game-theoretic approach, the model analyzes interactions under both stable and recessionary economic conditions. The results show that taxation often reduces the profitability of hotels without meaningfully increasing government revenue, especially during economic downturns. Green hotels are more severely affected, as they face higher costs while struggling to maintain competitive pricing in times of crisis. Meanwhile, OTAs benefit disproportionately from government interventions, amplifying structural imbalances in the supply chain. These findings highlight the need for more nuanced government policies, including targeted tax relief and sustainability incentives, to support green innovation while preserving the financial health of tourism businesses.